Optimal social distancing and the economics of uncertain vaccine arrival. (7th August 2022) - Iverson, Terrence; Karp, Larry; Peri, Alessandro
Abstract: We analytically identify two mechanisms that explain why a later arrival time for a pandemic‐ending vaccine has an ambiguous effect on optimal social‐distancing policy. We assess the net effect of these channels using a quantitative model solved for over a thousand parameter combinations. Optimal policy and welfare comparisons are both highly sensitive to beliefs about vaccine arrival. A policy of moving quickly to herd immunity by requiring social distancing for only the most vulnerable might be loosely justified for expected vaccine arrivals over 2 years, but becomes catastrophic if the expected arrival is within a year.